Grazing-incidence small-angle neutron scattering at high pressure (HP-GISANS): a soft matter feasibility study on grafted brush films - Vagias, Apostolos N.; Manouras, T.; Buchner, A.; Gutfreund, P.; Porcar, L.; Jacques, M.; Chiappisi, L.; Kosbahn, D. P.; Wolf, M.; Guasco, L.; Dahint, Reiner; Vamvakaki, M.; et al. (Journal of applied crystallography, 2024)
Grazing-incidence small-angle neutron scattering (GISANS) under pressure (HP-GISANS) at the solid (Si)-liquid (D2O) interface is demonstrated for the pressure-induced lateral morphological characterization of the nanostructure in thin (<100 nm) soft matter films. We demonstrate feasibility by investigating a hydrophobic {poly[(2,2,3,3,4,4,5,5-octafluoro)pentyl methacrylate]} (POFPMA)-hydrophilic {poly[2-(dimethylamino)ethyl methacrylate]} (PDMAEMA) brush mixture of strong incompatibility between the homopolymers, anchored on Si, at T = 45°C for two pressures, P = 1 bar and P = 800 bar. Our GISANS results reveal nanostructural rearrangements with increasing P, underlining P-induced effects in tethered polymer brush layers swollen with bulk solvent.
Gesehen am 05.09.2025